Bibiliometrics Menggunakan Analisis R-Bibiloshiny Resistensi Insulin pada Obesitas Kelompok Dewasa Database Scopus (2019-2025) - Krish Naufal Anugrah Robby; Rachmad Gusti Irwansyah; Leersia Yusi Ratnawati; Candra Bumi; Irma Prasetyowati; Isa Ma’rufi; Dedek Sutinbuk; Farida Wahyu Ningtyias; Anita Dewi Prahastuti Sujoso; Dewi Rokhmah; Ida Srisurani Wiji Astuti (Jurnal Kesehatan Amanah, 2024)
contributing to the global burden of type 2 diabetes, cardiovascular diseases, and other metabolic complications. This bibliometric study aims to analyze trends, thematic focuses, and collaborations in scientific publications related to insulin resistance in adult obesity, utilizing data from the Scopus database covering the period from 2019 to 2025. Bibliometric tools such as RStudio, Biblioshiny, and VoS Viewer were employed to extract and visualize findings from 8,037 publications. The results reveal that research activity peaked in 2021, followed by a decline in subsequent years. Dominant keywords, such as "insulin resistance," "obesity," and "metabolic syndrome," highlight the clinical and metabolic focus of current research. Biomolecular markers, such as "glycated hemoglobin" and the "triglyceride-glucose index," reflect a growing interest in more precise diagnostic tools. The United States, China, and Italy emerged as major contributors, with journals like Nutrients and Frontiers in Endocrinology leading in publications. Despite significant progress, there remains a considerable gap, particularly in exploring the role of epigenetics and the microbiota in insulin resistance. Additionally, cross-disciplinary collaboration and participation from institutions in developing countries remain limited. This study emphasizes the importance of global, interdisciplinary efforts to address these gaps and drive innovation in interventions, providing a foundation for future research aimed at reducing the impact of insulin resistance in adult obesity.